DERIVATIONAL AND SEMANTIC RELATIONS OF WORDS IN A WORD CLUSTER (Modern education and development, 2025)
In linguistics, words do not exist in isolation. They form complex networks based on their structural formation and meanings. These networks, often called word clusters, are composed of words that are either derived from a common root or semantically related through usage and meaning. Understanding these clusters is essential for grasping how language evolves, how vocabulary expands, and how comprehension works in both native and second-language acquisition. This paper explores two main types of relationships in word clusters: derivational and semantic relations.